STUDI KOMPUTASI ALIRAN PEMANAS PADA INKUBATOR TELUR BERKAPASITAS 400 TELUR DENGAN MENGGUNAKAN SUMBER PANAS BUMI BERENTALPI RENDAH - Hendrarsakti, Jooned; Fachri, Muhammad Faisal; Lukmana, Muhammad Arifudin (Bina Teknika, 2017)
This study aims to analyze the possibility of using geothermal energy as an alternative energy source for the egg incubator hatchery with capacity of 400 eggs. Geothermal resource used in the process of retrofitting has a temperature of 70°C with a maximum flow of 2 liters/s in accordance with the data of geothermal resources at Tangeung - Cibugur, Cianjur regency.Based on the results of the feasibility studies that have been done, the source of geothermal energy can be used for heating egg incubator in order to reach adequate incubation conditions (temperature 36 to 38.5 ° C and a relative humidity of 50-60%). In the process of retrofitting, the design of the incubator used is forced draft incubator. Its components are heat exchanger, fans, and a water tray. The type of heat exchanger that used is cross flow, one fluid mixed, one fluid unmixed. It uses a staggered arrangement of copper pipe as a heat exchange surface.Incubator with geothermal energy is well used by using 5 fans with volume flow rate 0,0094 – 0,0141 m3/s on the condition of the inlet air temperature is 23-27°C and a minimum pipe temperature is 65°C.